Stanje na področju elektronskih vlog za izdajo gradbenega dovoljenja v Sloveniji - Germovnik, Neža (Gradbeni vestnik, 2014)
Architecture, engineering and construction (AEC) industry has experienced an increase in the volume of the interoperable information presented in the structured digital form. As a result, processes such as an electronic data exchange, e-work and e-business have been well established. It would be interesting to see whether similar principles of less time consuming, quality and low-cost services apply to the administrative procedures in the AEC. For this reason, the survey where administrative units were asked questions regarding the usage and pros and cons of the e-services had been carried out. In this paper, the results of the survey as well as legislation, issues and potential improvements of the e-services offered by administrative units (with the focus on the processes related to the AEC) are presented.
Keywords: application; building permit; civil engineering; e-poslovanje; e-services; gradbeništvo; gradbeno dovoljenje; vloga